More about Boy : Roald Dahl's tales from childhood - Dahl, Roald (London : Puffin Books, 2008)
Roald Dahl relates stories from his childhood, from visiting chocolate stores to confrontations with mean, old ladies, and discusses how they influenced his writing.
Starting-point -- Papa and Mama -- More about Mama -- Kindergarten, 1922-3 -- A grand time -- Llandaff Cathedral School, 1923-5 (age 7-9) -- The bicycle and the sweet-shop -- The great mouse plot -- A life without sweets -- Going to Norway -- The magic island -- A visit to the doctor -- The last lap -- St. Peter's, 1925-9 (age 9-13) -- First day -- Writing home -- The matron -- Homesickness -- A drive in the motor-car -- The Maccano chariot -- Captain Hardcastle -- How I became a writer -- Little Ellis and the boil -- Goat's tobacco -- Repton and Shell, 1929-36 (age 13-20) -- Getting dressed for the big school -- Boazers -- Painful punishments -- The headmaster -- Chocolates -- Ten horrid little boys and girls -- Corkers -- Fagging -- That awful cold bath -- Games and photography -- Goodbye, school -- P.S. -- The voyage out (excerpt from Going Solo) -- A Dahl-tastic quiz.
Publisher's Weekly
6.5
5-8.
5-8
Keywords: Dahl, Roald -- Childhood and youth -- Juvenile literature; Dahl, Roald; Dahl, Roald; Authors, English -- 20th century -- Juvenile literature; Authors, English; English authors